2015
DOI: 10.1007/s40472-015-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive T Regulatory Cell Therapy for Tolerance Induction

Abstract: There is a clear need to develop strategies to induce tolerance without the need of chronic immunosuppression in transplant recipient and in patients with autoimmunity. Adoptive T regulatory cell (Treg) therapy offers the potential of long-lasting protection. However, based on results of clinical trials so far with ex vivo expanded autologous Tregs in type 1 diabetic (T1D) patients, it seems unlikely that single immunotherapy with Treg infusion without immunomodulation regimens that promote stable donor Treg e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 116 publications
1
6
0
Order By: Relevance
“…Hepatic immunoregulation on ethanol-induced steatosis 923 leads to increased immune tolerance after liver transplantation (13), chronic hepatitis virus infection (14), and hepatocellular carcinoma (15). A recent study indicated a significant decrease of peripheral blood Tregs in patients with alcoholic hepatitis, implying the significance of Tregs in the pathogenesis of ALD (16).…”
mentioning
confidence: 99%
“…Hepatic immunoregulation on ethanol-induced steatosis 923 leads to increased immune tolerance after liver transplantation (13), chronic hepatitis virus infection (14), and hepatocellular carcinoma (15). A recent study indicated a significant decrease of peripheral blood Tregs in patients with alcoholic hepatitis, implying the significance of Tregs in the pathogenesis of ALD (16).…”
mentioning
confidence: 99%
“…Overall, the Treg-resistant phenotype of Tcon cells appears to be relatively stable, able to persist in the absence of pro-inflammatory cytokines or other resistance-inducing factors. Future studies will need to assess the ability of Tcon cells to maintain Treg resistance, especially in light of efforts to use adoptive Treg therapy for treatment of autoimmune diseases ( 186 ). Infusion of Tregs into patients with Tcon cells resistant to suppression might prove to be ineffective, and should be examined further.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Regulatory T cells (Treg) play a central role in immune homeostasis and prevention of autoimmune diseases [1][2][3]. In a variety of transplantation and autoimmune mouse models, injection of Treg prevented immune pathology [4][5][6][7]. Promising clinical effects of Treg therapy with expanded Treg in the treatment of patients with graft versus host disease (GvHD) have been demonstrated [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Treg-based therapy could reduce toxicity and side effect in comparison with immunosuppressive drugs. The ultimate goal of Treg therapy would be induction of tolerance without immune suppression-related development of malignancies and infections [4,5,20]. Despite the current successes of Treg-based therapy, it is still not precisely known how and where immune regulation by injected Treg take place and in which anatomical side the inflammatory processes are controlled.…”
Section: Introductionmentioning
confidence: 99%